2013
DOI: 10.1155/2013/282870
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Emigration of Single-Positive Thymocytes

Abstract: T lymphopoiesis in the thymus was thought to be completed once it reaches the single positive (SP) stage, a stage when T cells are “fully mature” and waiting to be exported at random or follow a “first-in-first-out” manner. Recent evidence, however, has revealed that the newly generated SP thymocytes undergo a multistage maturation program in the thymic medulla. Such maturation is followed by a tightly regulated emigration process and a further postthymic maturation of recent thymic emigrants (RTEs). This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 147 publications
0
18
0
1
Order By: Relevance
“…are upregulated while others such as CD24 are down-regulated as DP cells mature into SP thymocytes32. Initially, the expression of CD24 and CD3 was analyzed on CD8 + SP cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…are upregulated while others such as CD24 are down-regulated as DP cells mature into SP thymocytes32. Initially, the expression of CD24 and CD3 was analyzed on CD8 + SP cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to fully mature SP thymocytes and thymic emigrants, which proliferate when triggered through the TCR. Subsequently, other groups have shown that a number of other cell surface proteins, including CD69 and various cytokine and chemokine receptors, change dramatically during maturation (Table I) (57). Mice expressing GFP under the control of the RAG1 or RAG2 regulatory elements have been instrumental in defining the temporal order of phenotypic changes during maturation, as RAG gene transcription is high in DP thymocytes, but acutely terminated upon positive selection.…”
Section: Acquiring the Competence To Dividementioning
confidence: 99%
“…Thymocytes that express a TCR with strong affinity to self-peptide presented by MHC die by negative selection (14). Positively selecting thymocytes undergo CD4-versus-CD8 lineage commitment (16), maturation (17, 18), and exit the thymus to become peripheral CD4 and CD8 T cells.…”
Section: Introductionmentioning
confidence: 99%